Pediatric Sleep Surgery - Sulman, Cecille G. (Frontiers in Pediatrics, 2014)
Adenotonsillectomy is the most common surgery performed for sleep disordered breathing with good outcomes. Children with obesity, craniofacial disorders, and neurologic impairment are at risk for persistent sleep apnea after adenotonsillectomy. Techniques exist to address obstructive lesions of the palate, tongue base, or craniofacial skeleton in children with persistent sleep apnea. Children with obstructive sleep apnea have a higher rate of peri-operative complications.